2014
DOI: 10.1177/1430.15819
|View full text |Cite
|
Sign up to set email alerts
|

Clinico-pathological Study of K-ras Mutations in Colorectal Tumors in Saudi Arabia

Abstract: K-ras mutations are common among the Saudi colorectal cancer population, especially pG12V and pG12D in codon 12, and are more frequent in sigmoid and rectal adenocarcinomas and stage IVB tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 20 publications
1
27
0
Order By: Relevance
“…However, tumors harboring KRAS mutations constitute a heterogeneous group of colorectal cancers. KRAS mutation frequency has been reported to be 31.9-56% by different studies (10,(14)(15)(16)(17). The present study was performed to determine the association of KRAS mutation status with demographic and clinicopathological characteristics and anatomical location of the tumor.…”
Section: Discussionmentioning
confidence: 92%
“…However, tumors harboring KRAS mutations constitute a heterogeneous group of colorectal cancers. KRAS mutation frequency has been reported to be 31.9-56% by different studies (10,(14)(15)(16)(17). The present study was performed to determine the association of KRAS mutation status with demographic and clinicopathological characteristics and anatomical location of the tumor.…”
Section: Discussionmentioning
confidence: 92%
“…The frequency of KRAS mutations varies worldwide, ranging from 13% to 56% (Roth et al, 2010;Montomoli et al, 2012;Murtaza et al, 2014;Zahrani et al, 2014;Peeters et al, 2015). The frequency of KRAS mutations (47.2%) in the current study was consistent with the published data from Asian countries (Asaka et al, 2009;Lin et al, 2011;Ahn et al, 2014;Tong et al, 2014), Western countries (Lamy et al, 2011;Vaughn et al, 2011;Bozzao et al, 2012), and the TCGA database (Cancer Genome Atlas Network, 2012) -but not with all reports (Liou et al, 2011;Chaiyapan et al, 2013;Phipps et al, 2013;Rosty et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In our review, considering all stages, noticeably lower frequencies of mutation have been reported in Pakistan (13%) [19], Morocco (24%) [22] and one study from Saudi Arabia (28%) [14], while higher frequencies have been reported in other studies from Saudi Arabia (56% & 41%) [13,18], Turkey (33%, 44% & 45%) [12,15,17] and Jordan (44%) [20]. In Oman, a ME country in the Gulf region, the frequency of mutation in 100 patients with unreported stage was 31% [21].…”
Section: Geographic Differences In Kras Mutation Ratesmentioning
confidence: 47%